2015
DOI: 10.1126/scitranslmed.aac4925
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab emtansine (T-DM1) renders HER2 + breast cancer highly susceptible to CTLA-4/PD-1 blockade

Abstract: Targeted drug delivery with antibody-drug conjugates such as the HER2-directed ado-trastuzumab emtansine (T-DM1) has emerged as a powerful strategy for cancer therapy. We show that T-DM1 is particularly effective in eliciting antitumor immunity in patients with early breast cancer (WSG-ADAPT trial) and in a HER2-expressing orthotopic tumor model. In the latter, despite primary resistance to immunotherapy, combined treatment with T-DM1 and anti-CTLA-4/PD-1 (cytotoxic T lymphocyte-associated protein-4/programmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
211
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(242 citation statements)
references
References 69 publications
9
211
1
2
Order By: Relevance
“…Preclinically, mirvetuximab soravtansine has been shown to activate monocytes and upregulate immunogenic cell death markers on ovarian tumor cells -providing a mechanistic rationale for combining this agent alongside a checkpoint inhibitor [88]. The outcomes of the mirvetuximab soravtansine-pembrolizumab combination study are expected to be informative as to the feasibility of combining the two treatment modalities in this indication, particularly in light of additional preclinical findings reporting that treatment with the maytansinoid-containing ADC ado-trastuzumab emtansine can elicit antitumor immunity and render HER2 + breast tumors susceptible to immune checkpoint inhibition [89].future science group www.futuremedicine.com …”
mentioning
confidence: 99%
“…Preclinically, mirvetuximab soravtansine has been shown to activate monocytes and upregulate immunogenic cell death markers on ovarian tumor cells -providing a mechanistic rationale for combining this agent alongside a checkpoint inhibitor [88]. The outcomes of the mirvetuximab soravtansine-pembrolizumab combination study are expected to be informative as to the feasibility of combining the two treatment modalities in this indication, particularly in light of additional preclinical findings reporting that treatment with the maytansinoid-containing ADC ado-trastuzumab emtansine can elicit antitumor immunity and render HER2 + breast tumors susceptible to immune checkpoint inhibition [89].future science group www.futuremedicine.com …”
mentioning
confidence: 99%
“…A preclinical in vivo study in mice has shown that the monoclonal anti-Her2 antibody-drug conjugate ado-trastuzumab emtansine (T-DM1) in combination with anti-CTLA4 or anti-PD-1 antibodies led to responses in xenografted tumors that had been resistant to T-DM1 monotherapy (97). The combination of trastuzumab with pembrolizumab is now investigated in a phase Ib-II trial (PANACEA trial, NCT02129556) in patients with metastatic Her-2 positive breast cancers resistant to trastuzumab (clinicaltrials.gov, accessed July 2, 2016).…”
Section: Perspectives: Combination Treatments To Increase Efficacymentioning
confidence: 99%
“…Another study showed combined treatment with ado-trastuzumab emtansine and cytotoxic T-lymphocyte antigen 4 plus programmed death 1 immune checkpoint inhibitors caused tumor rejection in a HER2-expressing orthotopic tumor model, triggering innate and adaptive immunity. 98 Preliminary data from an ongoing phase 1/2 clinical trial demonstrated that treatment with brentuximab vedotin plus nivolumab (anti-programmed death 1) in patients with relapsed or refractory Hodgkin's lymphoma resulted in 90% ORR and an acceptable safety profile. 99 ADCs are also being combined with other drugs, including brentuximab vedotin with modified doxorubicin, vinblastine, and dacarbazine and ado-trastuzumab emtansine with phosphoinositide 3-kinase or tyrosine kinase inhibitors.…”
Section: What's New For Adcs?mentioning
confidence: 99%
“…96 Research suggests ADCs may be synergistic with immune checkpoint inhibitors, providing a strong rationale for exploring these combination strategies. 97,98 Müller et al 97 recently showed that dolastatins (the family of microtubule inhibitors from which brentuximab vedotin, MMAE, is derived) combined with immune checkpoint inhibitors show synergistic antitumor activity and promote tumor destruction. Furthermore, ADCs coupled to MMAE induce dendritic cell (DC) homing in murine models, maturation of human DCs in lymphoma cell-DC co-cultures, and activation of T and B cells in patients, suggesting augmentation of tumor-specific immunity.…”
Section: What's New For Adcs?mentioning
confidence: 99%